Diabetic Macular Edema - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2007)
Diabetic retinopathy is the commonest cause of blindness in the working-age population all over the world. Poor glycemic control in diabetes is usually associated; with hypertension and increased blood lipid levels hence it is very important to control these risk factors during the management of diabetic retinopathy. The most frequent cause of significant and progressive visual loss is diabetic macular edema which may start from the very early stage of retinopathy resulting in central vision loss.